THE EXPLORATION OF UNIVERSITY STUDENTS’ PERCEPTIONS OF USING TECHNOLOGY IN ACADEMIC WRITING CLASSROOMS - Mali, Yustinus Calvin Gai (LLT Journal: A Journal on Language and Language Teaching, 2022)
This study explores university students’ perceptions of the usefulness of technology, the frequency of using technology, a technology tool that the students like the most, and perceptions if the technology they like the most helps them meet the characteristics of good writing. To meet the research goals, sixty-seven undergraduate students of a private university in Indonesia were asked to respond to a close-ended online questionnaire that surveyed their perceptions of using technology in their academic writing classroom. The findings indicate that an online dictionary, Google search engine, and Google translate are the technology that the students frequently use and consider useful to enhance their writing. Further, an online grammar checker is found to be a technology tool that the students like the most, and they feel that the tool can help them meet the characteristics of good writing. Recommendations for teaching practices using the technology and directions for further research are discussed.